Extubation Readiness in Preterm Infants: Evaluating the Role of Monitoring Intermittent Hypoxemia - Elie G. Abu Jawdeh; Amrita Pant; Aayush Gabrani; M. Douglas Cunningham; Thomas M. Raffay; Philip M. Westgate (MDPI AG, 2021)
Preterm infants with respiratory distress may require mechanical ventilation which is associated with increased pulmonary morbidities. Prompt and successful extubation to noninvasive support is a pressing goal. In this communication, we show original data that increased recurring intermittent hypoxemia (IH, oxygen saturation <80%) may be associated with extubation failure at 72 h in a cohort of neonates <30 weeks gestational age. Current-generation bedside high-resolution pulse oximeters provide saturation profiles that may be of use in identifying extubation readiness and failure. A larger prospective study that utilizes intermittent hypoxemia as an adjunct predictor for extubation readiness is warranted.